MEDIATION AS AN ALTERNATIVE TO RESOLVING ELECTRONIC BOOK COPYRIGHT DISPUTES FROM THE PERSPECTIVE OF USEFULNESS - Waruwu, Khamozaro (International Journal of Social Service and Research, 2024)
The research contributes to understanding and improving the regulation, practice, and institutionalization of electronic book copyright dispute mediation, aiming for a legally certain and effective resolution process. The research will be conducted through document analysis, involving a thorough examination of legal texts, regulations, case studies, and scholarly publications related to electronic books copyright and mediation practices. The results will be analyzed in terms of normative methods, legal cultural behaviors, and dynamics in practice, the implementation of mediation as a normative juridical procedural stage in reflection on institutional improvement, and the ideal procedural order and effectiveness of mediation in the two legal systems in the world.